Juridical Study Concerning Legal Responsibility in Used Car Sale and Purchase Agreements (Auto 2000 Rantauprapat Case Study) - Desi Anugrah Sari Harahap; Leli Sari; Muhammad Khoirul Ritonga (Dinasti Research, 2025)
This study uses a qualitative research method. The author took this qualitative method because there are several considerations and because the qualitative method is more able and easy to adjust when dealing with multiple circumstances, this method presents the essence of the relationship between researchers and respondents directly and this method is more sensitive so that it can adapt and sharpen many mutual influences on the value patterns faced by researchers. This research was conducted at Auto 2000 Rantauprapat located on Jl. SM. Raja, Bakaran Batu, Kec. Rantau Sel., Kab. Labuhanbatu, North Sumatra, the researcher conducted this research by going directly to Auto 2000 Rantauprapat to collect information and data through interviews with the owner of Auto 2000. Buying and selling is a transaction to replace or exchange goods based on the existence of an agreement, in order to meet someone's needs. In practice, buying and selling used cars can be done directly by the seller and buyer, but the seller and buyer have their respective rights and obligations. The formulation of the problem in compiling this research is: (1) what is the used car buying and selling agreement at Auto 2000 Rantauprapat, (2) what is the responsibility of the business actor if there is a default in the purchase of a used car. The research results obtained by researchers at Auto 2000 Rantauprapat are: (1) that the used car sales and purchase agreement (akad) at Auto 2000 Rantauprapat uses an agreement that is almost the same as other used car showrooms, namely the agreement (akad) is made verbally and reinforced with proof of purchase note, (2) the responsibility of the business actor in this case Auto 2000 Rantauprapat if there is a default is to remain fully responsible for the default that the business actor does and seek a solution together with its consumers, although according to the statement of the Auto 2000 Rantauprapat business owner since he started the business he has never committed a default against his consumers because Auto 2000 Rantauprapat explains and describes the condition of the car he sells as it is or according to the truth.